ANALISIS DAMPAK KRISIS KEUANGAN GLOBAL TAHUN 2008 TERHADAP GOLONGAN MENENGAH INDONESIA - Rahmad Igarta, Kisfendie Regga (IAIN Antasari, 2015)
Abstract: The increase in per capita income lead to poor grade into the middle class. This new middle class is vulnerable to the crisis on the economy because they are close to the poverty line. In 2008, the Indonesian economy is affected by the global ï¬nancial crisis. This study analyzes the Indonesian middle class households in 2005, 2008, and 2011 to determine the impact of the global ï¬nancial crisis. Middle class is deï¬ ned using no hierarchical cluster analysis (K-Means Cluster) based on spending patterns. Results of the comparison condition of the middle class in three years said that the global ï¬nancial crisis of 2008 affects the proportion of Indonesias middle class and its spending patterns. However, it has no effect on attention to education and health. This is due to middle class households have a head of household who are at their productive age to work and highly educated.